2005
DOI: 10.1038/modpathol.3800288
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and erythropoietin receptor expression in human prostate cancer

Abstract: Erythropoietin is a hematopoietic cytokine that regulates the production of red blood cells. Erythropoietin is normally produced in the adult kidney in a hypoxia-inducible manner. The recombinant form of human erythropoietin is in clinical use for the prevention and treatment of anemia that is associated with cancer and its treatment with chemoradiation therapy. A series of recent studies from our laboratory and others have reported the expression of receptors for erythropoietin in several different types of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
43
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 63 publications
11
43
0
2
Order By: Relevance
“…Several mechanisms of EPO involvement in tumor progression have been suggested: EPO increases EPOR expression in preexisting tumor cells, thereby increasing tumor growth and metastasis, or directly promotes tumor vascular angiogenesis (6,(8)(9)(10). In this study, we showed that EPO increases LEC density and tumor metastasis in lymph nodes.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Several mechanisms of EPO involvement in tumor progression have been suggested: EPO increases EPOR expression in preexisting tumor cells, thereby increasing tumor growth and metastasis, or directly promotes tumor vascular angiogenesis (6,(8)(9)(10). In this study, we showed that EPO increases LEC density and tumor metastasis in lymph nodes.…”
Section: Discussionsupporting
confidence: 49%
“…Although the exact mechanism of EPO-induced tumor progression remains to be understood, several mechanisms of EPO-induced tumor progression have been proposed. EPO may increase EPO receptor (EPOR) expression in preexisting tumor cells, thereby promoting tumor metastasis (6,(8)(9)(10). It increases the growth of tumors lacking EPOR through tumor angiogenesis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Following the detection of expression of Epo and its receptor on multiple cell types, it has become clear that Epo has pleiotropic effects extending well beyond the maintenance of red cell mass (3). In recent years, multiple investigators have documented the presence of EpoR expression in numerous tumor cell lines and carcinomata (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) but the specificity of commercially available EpoR antibodies has been questioned (15,16). Functional studies are needed to determine whether EpoR activation modifies tumor cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Erythropoietin (Epo), a principal cytokine involved in erythropoiesis, has been reported to promote the growth of malignant tumors by binding to its receptor (EpoR) through both autocrine stimulation of malignant cells themselves and paracrine route to the feeding microvessels due to the expression of both transcripts for Epo and EpoR mRNA in very many cancers [1][2][3][4] and for EpoR mRNA in the human endothelial cells of vein and artery [5]. However, there is controversy over the EpoR in cancer patients to be functional to develop their malignancies.…”
Section: Introductionmentioning
confidence: 99%